Pioneers of primetime [videorecording (DVD)] - Boettcher, Steven J.; Berle, Milton; Skelton, Red, 1913-1997; Hope, Bob, 1903-2003; Allen, Steve, 1921-2000; Caesar, Sid, 1922-2014; Davis, Sammy, Jr., 1925-1990; Ebsen, Buddy, 1908-2003; Rose Marie, 1923-2017; O'Connor, Donald, 1925-2003; Saperstein, Harlan (PBS Home Video, 2005)
A tribute to the icons of early television and an entertaining retrospective on the golden age of television comedy. Includes footage from shows such as "The Milton Berle show", "The Ed Sullivan show", "The Jack Benny show", "The Red Skelton show", "I love Lucy", and "The Honeymooners." Six years in the making, the program features exclusive in-depth interviews with an unprecedented collection of TV's early stars.